Description of the advertisement call of Rhinella mirandaribeiroi (Gallardo, 1965) (Anura: Bufonidae) - de Morais, Alessandro Ribeiro; Bastos, Rogério Pereira; Annunziata, Bruno Barcellos; de Carvalho Kokubum, Marcelo Nogueira; Maciel, Natan Medeiros (Zootaxa, 2012)
Currently, the Rhinella granulosa species group is composed by 13 species of toads (R. azarai (Gallardo); R. bergi (Céspedez); R. bernardoi Sanabria et al.; R. centralis (Narvaes & Rodrigues); R. dorbignyi (Duméril & Bibron); R. fernandezae (Gallardo); R. granulosa (Spix); R. humboldti (Gallardo); R. major (Müller & Helmich); R. nattereri (Bokermann); R. merianae Gallardo; R. mirandaribeiroi (Gallardo); R. pygmaea (Myers & Carvalho) that are distributed in South America and Panama (Narvaes & Rodrigues 2009; Sanabria et al. 2010). The advertisement calls have so far been described for the following species in the R. granulosa group R. azarai, R. bergi, R. centralis, R. dorbignyi, R. fernandezae, R. granulosa, R. major, R. merianae (São-Pedro et al. 2011; Guerra et al. 2011). Herein, we describe the advertisement call of R. mirandaribeiroi from Cerrado Biome, Central Brazil.